FRI0257 CAPILLAROSCOPIC VERY EARLY MORPHOLOGICAL AND QUANTITATIVE SPECIFIC ABNORMALITIES ANTICIPATE THE DEVELOPMENT OF THE "SCLERODERMA PATTERN" IN PATIENTS WITH RAYNAUD'S PHENOMENON. (2nd June 2020) - Pendolino, M.; Pizzorni, C.; Paolino, S.; Goegan, F.; Gotelli, E.; Schenone, C.; Cattelan, F.; Patanè, M.; Alessandri, E.; Sulli, A.; Smith, V.; Cutolo, M.
Abstract : Background: Nailfold videocapillaroscopy (NVC) abnormalities in subjects with isolated Raynaud's phenomenon (RP) may be present before transition to secondary RP(SRP) and development of a NVC "scleroderma pattern" and are known to predict for evolution to a connective tissue disease (CTD) within few years [1]. In a previous study, we have demonstrated that the very early increase of capillary diameter over 30 μm is an independent predictor for development of Systemic Sclerosis (SSc) associated SRP [2]. Objectives: Present pilot retrospective study aimed to investigate in a cohort of patients affected by CTD–related RP the presence of very early capillaroscopic morphological and quantitative abnormalities in the acquired pictures of NVC performed before the development of the NVC scleroderma-pattern. In particular, the study was addressed to identify a " very early" scleroderma pattern, in order to intercept patients with RP at high risk of evolution in a CTD, specifically SSc. Methods: We selected the NVCs of 273 SSc patients presenting one of the validated NVC "scleroderma patterns". We enrolled 26 SSc patients having a NVC analysis performed before the development of the "very early" NVC pattern. As controls, we evaluated 26 patients affected by other CTDs with stable non-scleroderma pattern over time. The 16 images per patient obtained by NVC examination were analyzed for total number of capillaries, number and the limbs diameters of capillaries with a diameter >30 μm, and microhemorrhages. Statistical analysis was performed using non-parametric tests. Results: All 26 SSc patients showed dilated capillaries with a diameter >30 μm in their previous NVC. Patients later developing scleroderma pattern had statically higher number and percentage of capillaries with a diameter >30 μm (p=0.0004 and p=0.0005), as well as a larger apical dilatation >40 μm (p=0.002). A progressive and significant increase in all capillary diameters were only detected in patients later diagnosed for SSc (apical p=0.006, venous p=0.02, arterial p=0.03). A significant homogeneous and progressive dilation was observed from the apical region and then involving both venous and arterial branches, only in SSc patients (p=0.002). Conclusion: Present pilot study demonstrates, for the first time that, before to develop a validated NVC scleroderma-pattern, all potential SSc patients present significant very early morphological and quantitative NVC changes. In particular, the progressive and homogeneous capillary loop dilation over 40 μm in over 40% of total number capillaries significantly could contribute to identify RP patients who will develop a SSc pattern after 4-5 years. References: [1]Cutolo M, Sulli A, Pizzorni C, Accardo S. Nailfold videocapillaroscopy assessment of microvascular damage in systemic sclerosis. J Rheumatol. 2000;27:155-60. [2]Trombetta AC, et al. J Rheumatol 2016;43:599-606. Disclosure of Interests: Monica Pendolino: None declared, Carmen Pizzorni: None declared, Sabrina Paolino: None declared, Federica Goegan: None declared, Emanuele Gotelli: None declared, Carlotta Schenone: None declared, Francesco Cattelan: None declared, Massimo Patanè: None declared, Elisa Alessandri: None declared, Alberto Sulli Grant/research support from: Laboratori Baldacci, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha